Effect of secondary emission on the afterglow of argon with negatively charged dust particles - Denysenko, I.B.; Stefanović, I.; Azarenkov, N.A.; Burmaka, G.P. (Вопросы атомной науки и техники, 2014)
A theoretical model for an argon/dusty plasma afterglow in presence of nano-sized dust particles with large density is developed. According to the model, in the plasma afterglow the electrons are generated in metastable collisions and in the secondary emission by collisions of ions with electrodes. By using the model and experimental time-dependencies for metastable density and electrode bias, the time-dependencies for electron density in argon/dusty plasma afterglow are calculated. The effect of secondary emission on electron generation in argon/dusty plasma afterglow is analyzed. Разработана теоретическая модель распадающейся пылевой аргоновой плазмы, которая имеет высокую плотность наноразмерных пылинок. Данная модель учитывает генерацию электронов при столкновениях метастабильных атомов между собой и благодаря вторичной эмиссии при столкновениях ионов с электродами. Используя эту модель и экспериментальные временные зависимости для плотности метастабильных атомов и потенциала электродов, рассчитаны временные зависимости для плотности электронов в пылевой распадающейся аргоновой плазме. Проанализировано влияние вторичной эмиссии на генерацию электронов в этой среде. Розроблено теоретичну модель пилової аргонової плазми, що розпадається, та має високу густину порошинок нанорозміру. Дана модель враховує генерацію електронів при зіткнені метастабільних атомів між собою та завдяки вторинній емісії при зіткнені іонів з електродами. Використовуючи цю модель та експериментальні часові залежності для густини метастабільних атомів та потенціалу електродів, розраховано часові залежності для густини електронів у запорошеній аргоновій плазмі, що розпадається. Проаналізовано вплив вторинної емісії на генерацію електронів у цьому середовищі.